(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the significance of dream motifs in psychological novels, focusing on their function in shaping the narrative and revealing the characters’ inner worlds. By analyzing the dream sequences in Oktam Usmonov’s novel "Girdob," we demonstrate how dreams serve as a powerful tool for: psychological exploration, narrative structure, symbolism and metaphor. The analysis of Saltanat’s dream in "Girdob" highlights the complex interplay between the conscious and unconscious mind, and how dreams can reflect the character’s emotional turmoil and psychological struggles. By examining the use of dream motifs in literary works, we can gain a deeper understanding of the human psyche and the power of storytelling.